2022
DOI: 10.1002/apj.2832
|View full text |Cite
|
Sign up to set email alerts
|

Activity and stability of castor oil‐based microemulsions with cellulose nanocrystals as a carrier for astaxanthin

Abstract: Microemulsions (MEs) are explored for its use in various food and drug formulations and applications. It is an amphiphilic material, consisting of oil phase, surfactant mixture, and aqueous phase. Castor oil (CO), which has antiinflammatory and analgesic activities, was used as the oil-phase in the ME formulations. Stability and activity of CO-based ME were investigated along with the influence of encapsulating astaxanthin as lipophilic drug and the use of cellulose nanocrystals (CNC) as pickering agent. Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…The four ME formulations were analyzed for the hydrodynamic diameter on day 1, 20, and 50 with storage conditions at 30 °C. Previous study of castor oil based ME showed insignificant changes in hydrodynamic diameter in various temperatures (−20, 4, 25, and 50 °C) [25].…”
Section: Stability Of Cto-based Mementioning
confidence: 71%
“…The four ME formulations were analyzed for the hydrodynamic diameter on day 1, 20, and 50 with storage conditions at 30 °C. Previous study of castor oil based ME showed insignificant changes in hydrodynamic diameter in various temperatures (−20, 4, 25, and 50 °C) [25].…”
Section: Stability Of Cto-based Mementioning
confidence: 71%